Ideas about the image of one's own body in women with physical activity - Zashchirinskaya O.V. ,; Zinovyeva E.V. ,; Medina Bracamonte N.A. ,; Kuznetsova I.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to broadening of perspectives on women's self-perception, with a focus on physical movement in daily life. Methods and structure of the study. The research encompassed 30 women between the ages of 20 and 30. The research employed the psychodiagnostic technique, the "ASI-R" questionnaire on body image perceptions, the «MAIA-R» multidimensional assessment of interoceptive body awareness, and the «5PFQ» five-factor personality questionnaire. Results and conclusions. For a period of two and a half months, a group of women aged between 20 and 30 (M = 24) underwent psychodiagnostics and kept a diary to explore their thoughts about their body image, taking into account their daily physical activity. The study revealed five key factors that influence women's perception of their body image: physical activity, a positive attitude towards physical contact, a lack of self-care, a busy social life, and a heightened awareness of their body. Young women who engage in physical activity, are conscious of their appearance, and enjoy physical contact tend to have a more positive body image.